Re-Evaluating Comparison between English and German: Indo-European Perspectives - Toyota, Junichi (Kalbotyra, 2008)
In this paper, English and German are compared historically along with other Indo-European languages (henceforth IE languages), focusing on their alignment changes. English and German are often compared, e.g. Hawkins (1986), but alignment is surprisingly not mentioned. This absence is perhaps because all of the modern IE languages have one type of alignment. However, historical comparison reveals that earlier IE languages had a different type, and the change from an earlier type to the modern one helps us to explain the current grammatical structure in English and German. This paper begins with a description of different alignment types which consequently raises various issues concerning variations of transitivity. Various differences in these types are described in detail. Then, the transitivity is compared in English and German. Once this comparison is explained historically, differences between these two languages appear clearly. This paper, based on comparative analysis, also mentions possible developmental paths for the future changes, especially in German.